Menumbuhkan Literasi Matematis Siswa dalam Pembelajaran Melalui Lensa Konstruktivistime - Dwi Aldi Hidayatulloh; Devi Rahayu Agustin; Fatus Atho’ul Malik (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
Mathematical literacy is a key competency of the 21st century, but student achievement in Indonesia is still low. The research aims to describe the constructivism approach in fostering students' mathematical literacy. The research method is qualitative with the type of literature study through the review of reputable articles indexed by Science and Technology Index and Scopus and relevant scientific books. The results showed that students experienced obstacles in solving mathematical literacy problems, including difficulties in interpreting problems, modeling contextual problems, drawing conclusions according to context, and understanding relationships between concepts. The constructivism approach based on Piaget and Vygotsky's theories can overcome obstacles through active learning, where students build knowledge through interaction with the environment and social experiences. To foster mathematical literacy through constructivism approach, teachers need to apply three main principles, namely authentic principle, scaffolding principle, and reflective principle. The three principles form a complementary pedagogical framework for building deep conceptual understanding and mathematical problem-solving skills.